Theorizing failure: explanations regarding weight regain among people with fat bodies. Issue 3 (August 2018) - Ekman, Aimée
Abstract Drawing on interviews with Swedish men and women who live in fat bodies, this article articulates people's own explanations of weight regain and failure to lose weight permanently. The aim is to give a glimpse into a system of explanations where eating is perceived as a way of handling other problems, fatness is considered as a symptom of something else, and where weight-reduction practices are seen as contributing to fatness. The participant's theorizations of weight regain, here calledtheorizing failure, are characterized by two types of shift in focus:cause -shifting andproblem -shifting . The first seeks to attribute fatness to causes outside the received view, focusing on behaviors and energy consumption. Cause-shifting means that overeating is seen as being caused by underlying problems. The second, problem-shifting, means that fatness is viewed as an effect of an underlying, 'real' problem, and defines fatness as a symptom, and weight-centered methods as part of the person's weight problem. This article pinpoints shortcomings with the weight-centered approach and addresses alternative ways to think about why some people fail to lose weight permanently.